Influência da clorexidina na resistência de união longitudinal à dentina: Estudo in vitro - Fonseca, Beatriz Maria [UNESP]; Bresciani, Eduardo [UNESP]; Pucci, César Rogério [UNESP]; Barcellos, Daphne Camara [UNESP]; Araújo, Maria Amélia Máximo de [UNESP] (Editora Cubo, 2017)
Objective: This study evaluated the effect of 0.2% chlorhexidine gluconate solution used as an therapeutic primer on the long-term bond strength of etch-and-rinse adhesive to dentin. Material and Methods: Bovine incisors were worn to expose an area of dentin and were divided into 2 groups: Group C (Control) - acid etching with 37% phosphoric acid + Single Bond; Group CHX (0.2% CHX) - acid etching with 37% phosphoric acid + 0.2% CHX for 30 s + Single Bond. Blocks of composite were fabricated and stored for 24 h or 6 months, sectioned into beams and submitted to microtensile tests. Results were analyzed by two-way ANOVA and Tukey tests. Results: Mean (±SD) values (in MPa) were as follow: Group CHX/24h - 41.8(±2.62)A; Group C/24h - 40.8(±3.35)AB; Group CHX/6 months – 36.4(±3.52)B; Group CHX/6 months - 26.1(±1.54)C. Conclusion: CHX improve the imediatte bond strength of resin-dentin and significantly lowered the loss of bond strength after 6 months water storage as seen in the control bonds.
Influence of chlorhexidine on longitudinal bond strength to dentin: In vitro study
Keywords: Chlorhexidine gluconate; Dentin; Tensile bond strength; Total-etch adhesives